2016
DOI: 10.1017/s0144686x16000192
|View full text |Cite
|
Sign up to set email alerts
|

How older adults would like falls prevention information delivered: fresh insights from a World Café forum

Abstract: Translation of falls prevention evidence into practice is problematic. Understanding older adults’ views about falls prevention information could enhance delivery of falls prevention, resulting in better engagement and uptake of recommended activities. The aim of this study was to examine the views and preferences of community-dwelling older adults about seeking and receiving falls prevention information. A community forum using a modified World Café approach was conducted. Participants discussed five topic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…The results of this study suggest that avoiding the f‐word (Yardley & Todd, ) may work for some, but clearly not for all older people. The overall variety of responses on the three AV messages confirms that it may be worthwhile providing future falls prevention information in several distinct formats (Khong et al, ), using precision health messaging to cater for the divergent variety of people's preferences. For example, different campaign message formats could be used to specifically target both people who have and who have not fallen (Khong et al, ) or signpost people both to readily available falls prevention resources and local opportunities as well as providing ready‐to‐use strategies.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…The results of this study suggest that avoiding the f‐word (Yardley & Todd, ) may work for some, but clearly not for all older people. The overall variety of responses on the three AV messages confirms that it may be worthwhile providing future falls prevention information in several distinct formats (Khong et al, ), using precision health messaging to cater for the divergent variety of people's preferences. For example, different campaign message formats could be used to specifically target both people who have and who have not fallen (Khong et al, ) or signpost people both to readily available falls prevention resources and local opportunities as well as providing ready‐to‐use strategies.…”
Section: Discussionmentioning
confidence: 72%
“…Previous research has also shown that it is hard to convince older adults that taking up falls prevention strategies will be effective for them personally (Haines et al, ) and that falls prevention information may be screened out or rejected by some older adults as unnecessary and not personally relevant (Hughes et al, ; Yardley et al, ), especially if they have not personally experienced a fall (Khong et al, ). Personal experience of having had a fall is considered a key influence on an older adult's decision to initiate seeking falls prevention information (Khong et al, ). The majority (72%) of the focus group participants had not experienced a fall in the past 12 months, which may explain why so many participants felt that the messages were not persuasive enough to do something about their falls risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations